Nonplanar 3D Printing of Epoxy Using Freeform Reversible Embedding. Issue 7 (27th January 2023) - Arun, Neeha Dev; Yang, Humphrey; Yao, Lining; Feinberg, Adam W.
Abstract: Thermally cured thermoset polymers such as epoxies are widely used in industry and manufacturing due to their thermal, chemical, and electrical resistance, and mechanical strength and toughness. However, it can be challenging to 3D print thermally cured thermosets without rheological modification because they tend to flow and not hold their shape when extruded due to cure times of minutes to hours. 3D printing inside a support bath addresses this by allowing the liquid polymer to be held in place until the thermoset is fully cured and expands the structures that can be printed as extrusion is not limited to layer‐by‐layer. Here, the use of Freeform Reversible Embedding (FRE) to 3D print off‐the‐shelf thermoset epoxy into lattice structures using nonplanar extrusion is reported. To do this, the authors investigate how extrusion direction in 3D space impacts epoxy filament morphology and fusion at filament intersections. Furthermore, the advantages of this approach are shown by using nonplanar printing to produce lattice geometries that show ≈ four times greater specific modulus compared with lattice structures printed using other materials and printing techniques. Abstract : Freeform Reversible Embedding (FRE) 3D printing is used to fabricate off the shelf thermally cured epoxy resin into high strength, lightweight lattice geometries using nonplanar 3D printing.